SOCIAL NETWORK MARKETING SYSTEMS: THE USE OF INSTAGRAM IN THE FASHION INDUSTRY - Nunu Andriani; Sidderatul Akbar; Melyana Ratana Pugu (CV. Adiba Aisha Amira, 2025)
In today’s digital age, where interactions between brands and consumers continue to adapt to the pace of technology, marketing strategies through social media, Instagram, have emerged as an important tool in building andining brand confidence in the fashion industry. The research method undertaken in this research is the study of literature by looking for literature that fits the context of the research. The findings of this research provide strategic insights for fashion industry practitioners in designing and implementing social network marketing strategies through Instagram to build and maintain brand confidence, by leveraging the power of visual content and influencer marketing effectively.